Silver bells [large type] - Raney, Deborah (Center Point Large Print, 2014)
"Two employees at a tiny weekly newspaper are strongly attracted to each other, but office policy forbids employee dating. As snow blankets the town, it seems that a relationship is out of reach... but they didn't count on a small Christmas miracle"--